Avaliação do efeito do galato de octila sobre a proliferação celular e metabolismo lipídico na linhagem de carcinoma hepatocelular HepG2 - Lima, Kelly Goulart (2018)
Octyl gallate (OG) is an antioxidant used in the food, cosmetic and medications industries that has shown antitumor effect on cell lineage of leukemia, melanoma and B cell lymphoma, as well as on animal model of pulmonary metastasis. Hepatocellular carcinoma (HC) is the main primary liver cancer affecting the world's population. Although surgical resection, ablation and liver transplantation are curative options, few patients are eligible for these therapies. The application of these therapeutic options is indicated only in the early stages of the disease and unfortunately most patients are diagnosed at advanced stage. In addition, there are reports in the literature of resistance to the only drug approved for systemic treatment, sorafenibe. In this study, we investigated the effect of OG on cell proliferation and lipidic metabolism in hepatocellular carcinoma HepG2 cells. Moreover, we developed a protocol for the quantitative evaluation of lipid droplets. We report, for the first time, that treatment with OG for 24 h inhibited HepG2 cell growth by decreasing mitochondrial activity and mass, which led to the reduction of ATP levels. This reduction in the energy supply triggered a decrease in Ki67 protein expression, leading to cycle arrest in S phase. In addition, the use of two treatments with OG with interval 24 hours induced loss of mitochondrial functionality and apoptosis without inducing resistance. These results showed that OG targets the mitochondria and is a candidate for new research on therapies for CH. We also report, for the first time, the effect of OG on lipidic metabolism, since our results showed that OG was able to increase the amount of lipids, triglyceride levels and the area of lipid droplets without involving the mTOR/SREBP-1c signaling pathway or modification of PPAR-α and PPAR-γ gene expression. As the ability of OG to inhibit mitochondrial activity and induce apoptosis is known, it is strongly suggested that reduction of mitochondrial fatty acid b-oxidation is involved in the OG mechanism in the accumulation of lipids. We also describe, for the first time, a protocol for the quantitative evaluation of lipid droplets using confocal laser scanning microscopy that compared to conventional fluorescence microscopy, provided great gain in the quality of the images.